2017
DOI: 10.19206/ce-2017-217
|View full text |Cite
|
Sign up to set email alerts
|

Concept of the exhaust system of combustion engines used in underground mining

Abstract: Analyses the problems occurring in the exploitation combustion engines used in mining have been presented in article. Design solutions used at present to protect the intake and exhaust systems of internal combustion engines operated in underground hard coal mines have been also described. A new design concept of exhaust system have been presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Kostopil for the six months of the analyzed period was 83 µg/m 3 and exceeded the recommended level by 2.1 times. The CAFE directive sets the average value of the concentration of particulate matter in the air at 25 µg/m 3 per year (Lesiak & Brzezański, 2017). The statistical analysis of air pollution by fine particulate matter PM2.5 showed that in the analyzed period of 164 days, there were bursts of concentration above 25 µg/m 3 for the entire measurement period.…”
Section: Results Of the Studymentioning
confidence: 99%
“…Kostopil for the six months of the analyzed period was 83 µg/m 3 and exceeded the recommended level by 2.1 times. The CAFE directive sets the average value of the concentration of particulate matter in the air at 25 µg/m 3 per year (Lesiak & Brzezański, 2017). The statistical analysis of air pollution by fine particulate matter PM2.5 showed that in the analyzed period of 164 days, there were bursts of concentration above 25 µg/m 3 for the entire measurement period.…”
Section: Results Of the Studymentioning
confidence: 99%